Performance Ongole Grade and Simmental Ongole Crossbred Cow at Village Breeding Center and Non Village Breeding Center at Special Region Yogyakarta, Indonesia - Baliarti, Endang (2014)
The research aims to determine cow performance of Ongole Grade (OG) and Simmental Ongole Crossbred cow (SOC) in terms of feed consumption, body condition score (BCS) and post partum estrus (PPE) at village breeding center (VBC) vs non village breeding center (NVBC). This research was conducted on April until December 2012 in 6 groups VBC (Sumber Ayu, Andhini Rahayu, Ngudi Makmur I, Andhini Mulyo, Trimanunggal Lembusuro, Trihandini Rejo) vs 2 groups NVBC (Sedyo Makmur, Andhini). The material used were OG (22 heads), SOC cow (16 heads) at VBC and OG (8 heads), SOC cow (10 heads) at NVBC. All the animals had been observed since the last pregnant period until PPE. Cow weight ranged from 260 kg to 380 kg with BCS score 2 to 3 on a scale of 5. Data of feed intake, BCS and PPE were collected and analyzed by randomized complete block design (RCBD) with location and cow factor by block. The feed intake of OG and SOC cow in term of dry matter (DM), crude protein (CP) and total digestible nutrients (TDN) was not different (P > 0,05). There were not significant different at BCS of OG and SOC cow at VBC vs NVBC from calving until PPE, the range BCS on a scale 2 to 2.8. Similarly, no significant identified between PPE of OG and SOC cow at VBC and at VBC in 105.42±30.75 days, 104±24,46 days vs 103.85±17.70 days, 110.57±14.60 days). It’s concluded that cow performance of OG and SOC cow were not significant different at VBC vs NVBC. Key Words: Performance, OG, SOC, VBC, NVBC